Growth Performance, Volatile Compound Production, and Pathogenicity Assessment of Jakaba BHP01 under Varying Culture Conditions - Rizka Aulian Kusuma; Elis Nina Herliyana; Surono; Abdul Munif (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2026)
Jakaba or Jamur Keberuntungan Abadi, classified in the Ascomycota phylum, is a fungus that is thought to have benefits in the form of nutrients for plants, and thus has the potential for further cultivation. The success of a pure culture depends on proper media preparation and the suitable environmental conditions for mycelial growth. Accordingly, this study investigated the growthcharacteristics of Jakaba BHP01 under different culture media, pH, and temperature conditions. Three factors were tested: media type (potato dextrose agar/PDA, malt extract agar/MEA, and malt peptone agar/MPA), media pH (pH 4, pH 6, and pH 8), and incubation temperature (10 ± 0.1 °C, 28 ± 0.1 °C, and 35 ± 0.1 °C ). Thus, there were 27 treatment combinations with three replicates.Macroscopic and microscopic observations revealed differences in colony texture, color, and hyphal characteristics under different treatments. The highest average diameter of Jakaba isolates was found in the M2P1S2 treatment combination, MEA medium, pH 4, and incubation temperature 28 ± 0.1 °C. The results of three-way ANOVA showed that the type of medium and pH did not have asignificant effect on the growth of Jakaba isolate diameter, while temperature had a significant effect (p < 0.0001). Pathogenicity tests on sengon seeds indicated that Jakaba BHP01 was nonpathogenic and significantly enhanced seedling length on MEA medium. Moreover, Jakaba BHP01 produced volatile compounds that inhibited Colletotrichum sp. pathogen growth by up to 38% onMEA. These findings provide preliminary baseline information for future studies on the cultivation and potential application of Jakaba BHP01 under controlled laboratory conditions in the future.